Improving Vocabulary Mastery Of The Seventh Year Students Using Scattergories Game In SMP Negeri 8 Palopo - Wiraldi Wiraldi; Muhammad Iksan; Jufriadi (Faculty of Education and Teacher Training of IAIN Palopo, 2020)
This thesis is about Improving Vocabulary Mastery of the Seventh Year Students Using Scattergories Game in SMP Negeri 8 Palopo. The problem statements of this research are Scattergories game effective in improving the students’ vocabulary mastery in SMP Negeri 8 Palopo. The objective of the research to find out whether or not s categories game effective in improving the students’ vocabulary mastery in SMP Negeri 8 Palopo. The research design used a pre-experimental design. The research instrument used a vocabulary test. From the findings, the researcher concluded that the use of the Scattergories game was effective in improving the vocabulary of students at SMP Negeri 8 Palopo. The increase in students' vocabulary after treatment, this can be proven by the results of the pre-test students with an average score of 58.8333 and an average post-test score of 85.7000, the value of t0 (t count) = 21.604 and df (degrees of freedom) based on these results, namely 21.604 ˃ 2.045, from these results the researcher concluded that t0 (t count) is higher than tt (t table), t0 ˃ tt. it means that there is a significant difference between vocabulary mastery before and after using the s categories game.